Etnosentrisme Konsumen, Kerentanan Pengaruh Normatif, Permusuhan Konsumen terhadap Kesediaan untuk Membeli - Ledy Yolanda; R. Arief Helmi; Rita Komaladewi; Fachri Eka Saputra (IPM2KPE, 2023)
This study aims to examine the impact of consumer ethnocentrism, vulnerability to normative influence, and consumer hostility towards purchasing foreign products in Indonesia in the context of Indonesian franchised products. This research method is quantitative. Questionnaires are used to collect sample data. 350 questionnaires were distributed by direct delivery survey to targeted respondents, and 208 were returned for processing. The data analysis used is PLS 3.3.0. The results showed, a) consumer ethnocentrism towards consumer hostility has a value of t count > t table, namely 2.193 > 1.96; b) susceptibility to normative influences on consumer hostility has a value of t count > t table, namely 2.144 > 1.96; c) consumer ethnocentrism towards purchasing foreign products has a value of t count > t table, namely 6.858 > 1.96; d) susceptibility to normative influence on the purchase of foreign products has a value of t count < t table, namely 0.827 < 1.96; e) consumer hostility towards purchasing foreign products has a value of t count > t table, namely 3.524 > 1.96. In conclusion, a) consumer ethnocentrism has a positive relationship with consumer hostility; b) susceptibility to normative influence is positively related to consumer hostility; c) consumer ethnocentrism has a negative relationship with purchasing foreign products; d) vulnerability to normative influences is not related to the purchase of foreign products; e) consumer hostility is negatively related to the purchase of foreign products. Keywords: Consumer Ethnocentrism, Susceptibility to Normative Influences, Purchase of Foreign Products, Consumer Hostility